Mali - Economic Policy and Public Finance Management Credit - Mastri, Lawrence (World Bank, Washington, DC, 2012)
The Economic Policy and Public Finance Management Credit (EPPFMC) was part of the Country Assistance Strategies (CAS) base case lending scenario of budget support operations. The thematic coverage of the EPPFMC focused on policy and institutional issues in macro, public finance, and selected sector areas. It complemented self-standing sector investment operations covering health, education, rural infrastructure, agricultural competitiveness, support to growth, and transport corridors. The EPPFMC aimed to: (i) promote growth and poverty reduction through (a) strengthening macroeconomic and fiscal management and (b) implementing key actions underpinning Mali's long-term growth and competitiveness; and, (ii) improve efficiency, accountability, and transparency in public finance management through strengthening (a) public expenditure management at central and decentralized levels and (b) the public procurement system. Some of the lessons are as follows: (a) The operation demonstrated the merits of including in Mali's policy-based lending operations, policy and institutional reform measures complementary to and supportive of ongoing sector operations. (b) For a country such as Mali, with weak institutional and administrative capacities, it is important to be realistic on what can be achieved, and be selective on which issues are undertaken within a short timeframe. This lesson was adhered to in the EPPFMC. (c) Policy measures should be better matched to the objectives sought. In the Mali cotton case, although the cotton reform actions were and continue being implemented, the cotton sector remains in a precarious financial situation due not only to weak management but also to (a) stagnant or adverse international cotton prices and (b) an appreciating currency, resulting in lower local-currency denominated revenues on marketed cotton.